2022
DOI: 10.1161/jaha.121.024992
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Cilostazol Added to Aspirin or Clopidogrel for Secondary Prevention After Noncardioembolic Stroke

Abstract: Background The objective of the study was to assess the cost‐effectiveness of cilostazol (a selective phosphodiesterase 3 inhibitor) added to aspirin or clopidogrel for secondary stroke prevention in patients with noncardioembolic stroke. Methods and Results A Markov model decision tree was used to examine lifetime costs and quality‐adjusted life years (QALYs) of patients with noncardioembolic stroke treated with either aspirin or clopidogrel or with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Yet another study has previously demonstrated that the addition of cilostazol to aspirin or clopidogrel is cost-effective in patients with non-cardioembolic strokes. 28 However, no previous stroke studies have compared cost-effectiveness of genotype-guided therapy with empiric ticagrelor and aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another study has previously demonstrated that the addition of cilostazol to aspirin or clopidogrel is cost-effective in patients with non-cardioembolic strokes. 28 However, no previous stroke studies have compared cost-effectiveness of genotype-guided therapy with empiric ticagrelor and aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian group 25 has previously shown that genotype guided therapy with patients with LOF mutations being given ticagrelor is cost effective at a threshold of $50,000 CAD per QALY. Yet another study has previously demonstrated that the addition of cilostazol to aspirin or clopidogrel is cost effective in patients with non-cardioembolic strokes 26 . However, no previous stroke studies have compared cost effectiveness of genotype guided therapy with empiric ticagrelor and aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that single aspirin is more effective than clopidogrel [10,11]. Several trials have tested the efficacy and safety of clopidogrel and aspirin versus aspirin in preventing recurrent stroke in ischemic stroke [12][13][14]. A metaanalysis from 2018 found that an aspirin-clopidogrel combination given within 24 hours of an ischemic stroke also reduced the risk of recurrent stroke [15].…”
Section: Introductionmentioning
confidence: 99%